The Haptic and the Phatic in the Era of Globalization - Arjun Appadurai (Glocalism: Journal of Culture, Politics and Innovation)
Touch is a universal faculty which lets humans explore intimacy, danger and other aspects of their sensory worlds. In India, the regulation of touch is the key to the maintenance of a highly hierarchical, unjust and humiliating social system. Today, the spread of haptic technologies further complicates the relationship between human beings, machines and the paradoxes of intimacy.